Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1037/1064-1297.8.4.451
|View full text |Cite
|
Sign up to set email alerts
|

Separation of drug effects on timing and behavioral inhibition by increased stimulus control.

Abstract: Impulsive behavior may represent, in part, a failure of behavioral inhibition (the ability to delay or inhibit a response). In this study, use of a multiple signaled-unsignaled differential-reinforcement-of-low-rates (DRL) 15-s schedule allowed examination of drug effects in conditions in which level of stimulus control differed. Results showed that whereas diazepam increased premature responding during signaled and unsignaled DRL components, amphetamine and delta9-tetrahydrocannabinol increased premature resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…This is unusual because previous studies have shown that a reduction in DRL efficiency is usually accompanied by an increase in burst responding, a pattern that can be induced by administration of psychostimulants (e.g., Cheng et al 2006a). The prevailing explanations for this pattern of responding are either that these drugs accelerated the speed of an internal clock and/or increased impulsivity, which in turn would decrease response efficiency (e.g., Meck 1996;Wiley et al 2000;McAuley et al 2006;Matell and Portugal 2007). Both of these explanations are likely to be inappropriate in the present situation because of the observation that SUP-male rats display the same temporal accuracy with increased precision compared with CON-male rats when assessed in other reproduction tasks such as the peak-interval procedure (e.g., Meck and Williams 1997a;Cheng et al 2006b;Cheng and Meck 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is unusual because previous studies have shown that a reduction in DRL efficiency is usually accompanied by an increase in burst responding, a pattern that can be induced by administration of psychostimulants (e.g., Cheng et al 2006a). The prevailing explanations for this pattern of responding are either that these drugs accelerated the speed of an internal clock and/or increased impulsivity, which in turn would decrease response efficiency (e.g., Meck 1996;Wiley et al 2000;McAuley et al 2006;Matell and Portugal 2007). Both of these explanations are likely to be inappropriate in the present situation because of the observation that SUP-male rats display the same temporal accuracy with increased precision compared with CON-male rats when assessed in other reproduction tasks such as the peak-interval procedure (e.g., Meck and Williams 1997a;Cheng et al 2006b;Cheng and Meck 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Modified response efficiency is de-fined as the ratio between reinforcement rate and overall response rate after the subtraction of burst responses-defined by lever presses with an inter-response time (IRT) <2 sec. Burst responding was excluded in determining the modified response efficiency, because previous studies have suggested that these rapid responses are more related to behavioral inhibition and emotional reactivity (e.g., frustration, impulsivity, and the failure of self-control) than to timing or temporal memory per se (e.g., Wiley et al 2000;Cheng et al 2006a). Therefore, it seems reasonable to dissociate burst responding from response efficiency and to treat both measures independently when evaluating performance on DRL schedules.…”
mentioning
confidence: 99%
“…However, because MK-801 and other NMDA receptor antagonists can increase general activity (Adriani et al, 1998;Mele et al, 1996;Miller et al, 2006;Tonkiss et al, 1988;Whishaw & Auer, 1989;Wozniak, Olney, Kettinger, Price, & Miller, 1990), an alternative explanation of a leftward shift in IRTs is that it indicates a general reduction in the ability to withhold (inhibit) a response (Wiley, Compton, & Golden, 2000). This alternative explanation is important because DRL performance does not clearly separate changes in internal timing from changes in response inhibition.…”
mentioning
confidence: 99%
“…In the RI task, differences in the length of time between reward delivery (ie, under different delay conditions) could impact the motivation to respond. In addition, external signals, such as the houselight, that explicitly signaled the premature phase may interact with the pharmacological effects of amphetamine (Wiley et al, 2000). The latter possibility is particularly intriguing in that amphetamine produced opposing effects on impulsive choice when a houselight was present or absent during the delay to reward delivery (Cardinal et al, 2000).…”
Section: Amphetamine-induced Changes In Impulsive Action May Interactmentioning
confidence: 99%
“…Performance improves (ie, impulsivity decreases) in a 15-s DRL task when a cue is presented at the end of the delay (Carey and Kritkausky, 1972), suggesting that attending to an external sensory cue improves performance at intermediate delays. More importantly, amphetamine does not produce a leftward shift in IRTs when a signal is present (Wiley et al, 2000), although it does increase the response rate and decrease the number of reinforcers obtained, a pattern of deficits that points to elevated impulsivity but no alteration in timing abilities. The findings also fit with our idea that the effect of a drug on impulsive action (or any other response) depends on the cognitive process that is controlling behavior.…”
Section: Amphetamine-induced Changes In Impulsive Action May Interactmentioning
confidence: 99%